Poorly differentiated and undifferentiated (anaplastic) carcinoma of thyroid with diagnostic challenges: A case series - Shit, Arundhati; Soumita Ghosh Sengupta,; Abhishek Bandyopadhyay,; Raychaudhuri, Gargi (Asian Journal of Medical Sciences, 2024)
Poorly differentiated thyroid carcinoma (PDTC) and anaplastic or undifferentiated thyroid carcinomas (ATC) are uncommon malignancies of the thyroid. Anaplastic thyroid cancers represent only 1–2% of all thyroid cancer diagnoses; however, they contribute to 14–50% of fatalities associated with thyroid cancer, with a median survival duration ranging from 3 to 5 months. The majority of patients diagnosed with this disease are aged 65 years or older. Most patients exhibit a rapidly enlarging neck mass, difficulties in swallowing, or alterations in their voice. The 2022 World Health Organization classification introduced PDTC as a subtype of high-grade follicular cell-derived thyroid carcinoma (HGFCTC), whereas also renaming ATC as anaplastic follicular cell-derived thyroid carcinoma. There are evidence which suggests stepwise molecular progression from well-differentiated carcinoma to HGFCTC to ATC manifested by alteration in the MAPK pathway especially BRAF and RAS mutations and gain of secondary aggressive molecular signatures. PDTCs and ATCs are difficult to diagnose due to their rarity and previous equivocal diagnostic criteria. The aim of this study is to present a series of rare and interesting cases of PDTC and undifferentiated/anaplastic thyroid carcinoma accompanied by a concise literature review.